Pengaruh Umur Perusahaan, Kebijakan Dividen, dan Ukuran Perusahaan terhadap Nilai Perusahan pada Perusahaan Manufaktur Yang Terdaftar di BEI - Makdalena Pransina Bibaborbir; M. Bahril Imiddaviq (BISMA : Business and Management Journal, 2025)
The Influence of Firm Age, Dividend Policy, and Firm Size on Firm Value in Manufacturing Companies Listed on the Indonesia Stock Exchange. Undergraduate Thesis, Accounting Study Program, Faculty of Economics, Universitas Islam Majapahit (UNIM). The Indonesian capital market has experienced rapid growth, marked by increased investor participation and the complexity of financial decisions. Firm value has become the primary focus as it reflects long-term prospects and performance. This study examines the influence of firm age, dividend policy, and firm size on firm value in the manufacturing sector listed on the Indonesia Stock Exchange (IDX). The sample consists of 48 firms from the 2022–2024 period using purposive sampling. The analysis uses path analysis (SPSS 22). The results reveal that company age does not have a significant effect on company value. Conversely, dividend policy and company size are found to have a significant effect on company value.